(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
From December 14, 1941, workers of military enterprises had the status of being mobilized for war; in 1941, 18,765 people completed these courses; enterprises of the People’s Commissariats of the Center fulfilled military production plans in July by 66.9%, in August by 31.8%, in September by 50%.